Study on non-verbal communication knowledge among doctors of non-clinical and para clinical departments of Government Vellore medical college hospital, Vellore, Tamil Nadu, India - J., Balaji; P., Parthiban (International Journal of Research in Medical Sciences, 2019)
Background: Many Studies and Research Articles in our medical field focuses on Verbal Communication component. The Non-Verbal Component has been neglected in many circumstances. But Medical science endorses that Non-Verbal component plays a major role in the communication process in all set ups whether it is in the classrooms, Examination Hall, Outpatient Room or Wards or Intensive Care Units. The objective of this study is to access the knowledge and Awareness of NVC Component among Doctors of Non-Clinical and Para Clinical Departments of GVMCH - Vellore, Tamil Nadu, India. Methods: This Cross-Sectional Study was conducted among 45 Doctors across 7 Departments of Government Medical College Vellore. Mean, Median, Mode and Standard Deviation were used for quantitative Data and Pearson Chi Square Test and Logistic regression was used for qualitative Data using Trial Version of SPSS 22. Results: The mean Score was 7.2±2.8 with Mean scoring percentile of 28.8 ±11.5. There was Pearson’s Chi Square significance for Variables like External Resources related to NVC, Books related to NVC, UG and PG pursued at, Exposure to Workshops or CME s related to NVC, and age Group < 35. But on running Logistic Regression we got statistical significance for variables like External resources related to NVC, UG studied at same state, Age Group >35 years. Conclusions: Variables like External resources, UG studied at same state, Age Group >35 years Showed Statistical significance in knowledge on Non-Verbal communication in this Study set up.